2008
DOI: 10.5628/rpcd.08.01.34
|View full text |Cite
|
Sign up to set email alerts
|

Prontitud Coordinativa: perfiles multivariados en función de la edad, sexo y estatus socio-económico

Abstract: Coordination readiness: multivariate profiles based upon age, sex, and socioeconomic status Purpose: To describe motor coordination levels (CoM), their centile distribution, as well as identify the coordinative readiness of Peruvian children as a function of age, sex and socioeconomic status. Methodology: Sample size included 4007 children (n=1889 females; n=2118 males) between 6 and 11 years of age (young = 8,99; children = 9,07) from several schools of the metropolitan area of Lima, Perú. CoM was assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 9 publications
4
7
0
12
Order By: Relevance
“…Also in German children, aged 6-10 years, Willimczik (1980) did not find significant differences between the sexes in MC scores. On the contrary, significant age changes and some sex differences were found in 4007 Peruvian children, aged 6-11 years (Valdivia et al, 2008b).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Also in German children, aged 6-10 years, Willimczik (1980) did not find significant differences between the sexes in MC scores. On the contrary, significant age changes and some sex differences were found in 4007 Peruvian children, aged 6-11 years (Valdivia et al, 2008b).…”
Section: Discussionmentioning
confidence: 91%
“…Our finding did not support previous research by Vandendriessche et al (2012), who observed that high SES girls were more proficient than their peers from middle SES in JS, WB and HH. Valdivia et al (2008b) reported that SES was not a relevant predictor of differences in MC profiles of Peruvian children. One plausible explanation for the Madeira data is that low SES children had a more permissive rearing atmosphere that might be conducive to greater freedom of activity and opportunity for practice and, in turn, compensate the higher MC noted in low SES (Malina et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Os estudos que propuseram estabelecer valores de referência de seus países, visando facilitar um diagnóstico e um perfil de desempenho coordenativo, segundo os testes do KTK, mais adequados para as suas realidades (Valdivia et al, 2008a;Valdivia et al, 2008b;Vidal et al, 2009;Vandorpe et al, 2010 Ribeiro, A.C. David, M.M. Barbacena, M.L.…”
Section: Estudos Para Construção De Dados Normativos Da Bateria Do Ktunclassified
“…Um ponto interessante de se observar em relação à magnitude dos desvios-padrão para os testes de saltos laterais é a elevada variabilidade inter-indivíduos encontrados em cada faixa etária. Tais resultados foram observados, similarmente, em alguns estudos 8,9,19,28 . Essa variabilidade reflete as mudanças que ocorrem na coordenação motora, o que demonstra a necessidade de um planejamento cuidadoso das atividades motoras para crianças nessas faixas etárias, uma vez que idade não necessariamente prediz o nível de desenvolvimento.…”
unclassified